Recent advances in passive UHF-RFID tag antenna design for improved read range in product packaging applications: a comprehensive review - Rawad, Abdulghafor; Sherzod Turaev, Sherzod; Hamad, Almohamedh; Rana, Alabdan; Badr, Almutairi; Abdulrazaq, Almutairi; Sultan, Almotairi (IEEE, 2021)
Radio frequency identification (RFID) is a rapidly developing technology, and RFID sensors have become important components in many common technology applications. The passive ultra-high frequency (UHF) tags used in RFID sensors have a higher data transfer rate and longer read range and usually come in unique small and portable application designs. However, these tags suffer from significant frequency interference when mounted on metallic materials or placed near liquid surfaces. This paper presents the recent advancements made in passive UHF-RFID tag designs proposed to resolve the interference problems. We focus on those designs that are intended to improve antenna read range as well as scalability designs for miniaturized applications